A transcutaneous vagus nerve stimulation study on verbal order memory. (August 2021) - Kaan, Edith; De Aguiar, Ivette; Clarke, Christina; Lamb, Damon G.; Williamson, John B.; Porges, Eric C.
Abstract: Transcutaneous vagus nerve stimulation (tVNS) is a non-invasive, well-tolerated and inexpensive technique to stimulate the norepinephrinergic and other pathways in the brain. These pathways serve brain areas implicated in memory, emotion and cognitive control. We investigated the effect of tVNS on the ability of healthy adults to recall the order of words in a word list. Healthy young adults were tested in two sessions, once with tVNS (tragus), once with sham (earlobe) stimulation, counterbalanced over sessions (N = 29). A separate group (N = 33) received no stimulation. Between-group comparisons showed that tVNS was associated with higher accuracy on the order memory task, but only when the items were phonologically similar. These results are interpreted as supporting the idea that tVNS enhances selective attention and inhibitory control when required by the task. tVNS is therefore a promising method for neuromodulation of language and memory, and for the development of methods to enhance memory and learning of language, and other skills. Highlights: TVNS enhances memory for the order of words when words are phonologically similar. This supports the idea that tVNS affects attention and cognitive control. TVNS is a promising method for language and memory training and rehabilitation.